Influence of oropharyngeal therapy with mother’s own milk on the microbiome and metabolome of very preterm infants: a pilot study - Xiu, Wenlong; Yang, Changyi; Lin, Xiaojun; Zhang, Baoquan; Chen, Rong (Frontiers in Nutrition, 2025)
BackgroundOropharyngeal therapy with mother’s own milk (OPT-MOM) may serve as a promising therapeutic approach to elicit immunoprotective and anti-inflammatory benefits for preterm infants.ObjectivesThis prospective pilot study aims to investigate whether OPT-MOM alters the oral microbiota, gut microbiota and metabolic profiles in very preterm infants.MethodsThe eligible infants were divided into two groups: the OPT-MOM group and the control group. The OPT-MOM group received oropharyngeal administration with mother’s own milk every 3 h, starting within the first 48 h after birth and lasted for 14 days. Salivary samples and fecal samples from both groups were collected to detect microbes using 16S rRNA gene sequencing, while fecal metabolomics was measured by untargeted liquid chromatograph-mass spectrometer.ResultsA total of 26 very preterm infants were enrolled in the study, with 13 assigned to each group. Our study identified distinct oral and intestinal microbiome profiles in OPT-MOM group compared to the control group. Briefly, the relative abundance of the Escherichia-Shigella and Enterobacter genera was significantly reduced in the oral cavity of preterm infants in the OPT-MOM group, while the abundance of the Rothia genus increased markedly. After 14 days of intervention, the gut microbiota of preterm infants in the OPT-MOM group exhibited a significant decrease in the abundance of the Proteobacteria phylum and a concomitant increase in the abundance of the Firmicutes phylum, which emerged as the dominant phylum. Additionally, the OPT-MOM group showed a significant increase in the relative abundance of Streptococcus and Staphylococcus genus, while a significant decrease in Enterococcus and Enterobacter genus abundance was observed in the gut microbiota. The predominant bacteria in the oral microbiota of preterm infants are highly similar to those in the intestinal microbiota. Metabolomic profiling identified that the OPT-MOM group demonstrated significantly higher levels of multiple potentially beneficial metabolites, including N-acetylneuraminic acid, myristoylcarnitine, lauroylcarnitine, acetylcarnitine, and 2,4-dihydroxybutanoic acid.ConclusionAdministration of OPT-MOM could promote the establishment of favorable microbial communities in both oral and intestinal ecosystems of preterm infants, potentially facilitating the production of metabolites that are crucial for infant health.